Attitude of Iranian medical specialty trainees toward providing health care services to patients with mental disorders - Movahedi, Sana; Shariat, Seyed Vahid; Shalbafan, Mohammadreza (Frontiers in Psychiatry, 2022)
Introduction The stigma of mental illness has a negative impact on the diagnosis and treatment of these disorders. Considering the high prevalence of mental illness, the attitude of medical specialists toward mental disorders, who are front liners in diagnosing and treating these patients, is critical. Therefore, we examined the attitude of Iranian medical specialty trainees toward providing health care services for patients with mental illness. Methods We included 143 residents in the fields that have the most interactions with patients with mental disorders, including internal medicine, surgery, neurology, cardiovascular diseases, and psychiatry. A demographic checklist, as well as the opening minds scale for health care providers stigma assessment questionnaire, was provided, which measures five dimensions of improvement, social responsibility, social distance, exposure, and other (such as risk) in health care providers toward delivering the healthcare services to patients with mental disorders. Results The mean score of stigma for mental illness in medical specialty trainees was 61.36 ± 4.83 out of 100. Psychiatric residents have the least stigmatizing attitude (58.38 ± 3.54), and internal medicine and cardiology residents have the highest score, respectively, (62.96 ± 6.05, 62.45 ± 3.80). As for comparing subscales between specialties, only the social responsibility subscale showed a significant difference, with psychiatry having less stigma toward social responsibility (12.93 ± 2.01) than cardiology (15.09 ± 1.50) trainees. Conclusion The attitude of medical specialty trainees toward providing health care services for patients with mental illness is not uniform; internal medicine and cardiology residents have more stigmatizing attitude, while psychiatric residents have less stigmatizing attitude. It seems that not every contact could be useful in making a better attitude toward mental illness, but it needs preconditions, like a structured contact that leads to positive outcomes. Anti-stigma interventions are needed to improve the attitude of medical specialty trainees toward providing health care services to patients with mental illness.